NURSES' PERCEPTIONS OF THE RELEVANCE OF TOPICS IN MICROBIOLOGY TO NURSING PRACTICE (International Journal of Functional Research in Science and Engineering (IJFRSE), 2024)
Microbiology courses are an essential component of the Nigerian nursing training program. This study explored nurses' perceptions of the importance of microbiology topics in nursing practice. One hundred ninety-eight Registered Nurses (RNs) practicing in various institutions in Edo state, Nigeria, completed the survey. A Likert-type scale rated 1 (no significance) to 5 (extreme significance) was used to ascertain the relevance of various microbiological topics. The highest-rated topics were infection control, hospital-acquired infections, disease transmission, and handling of patient specimens. The lowest-rated were microscope use and the Gram stain procedure. In addition, the respondents expressed little interest in molecular testing methods. Thus suggesting a gap in their understanding of the uses of these tests, which could be bridged in a microbiology course. The present study suggests that nurses are most interested in microbiology topics that significantly impact patient care. The findings have implications for improving teaching in microbiology education in pre-nursing and nursing curricula.